2013
DOI: 10.2306/scienceasia1513-1874.2013.39.012
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-matrix metalloproteinases activities of dried longan (Euphoria longana) seed extract

Abstract: Longan, a major fruit crop in Thailand, is a rich source of antioxidant polyphenic compounds, mostly gallic acid and ellagic acid. Dried longan seeds contain large amounts of antioxidant polyphenols. In this study, three fractions of dried longan seed extract were collected by Sephadex LH-20 column chromatography to determine the major compounds in each, and the amounts of gallic acid and ellagic acid were quantified. The first fraction was determined to be the major source of gallic acid, while ellagic acid w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Although D. longan leaves were reported to contain gallic acid, but the other active compounds for anti-aging in the leaf might be more potent than gallic acid due to the activities themselves or synergistic effects of other phenolic or active compounds consisting in the extracts. While inhibition of collagenase activity of D. longan leaf extract has not been reported to date, Panyathep et al (2013) revealed the inhibition of MMP-13 of D. longan seed extracts. The gallic acid-enriched and ellagic acid-enriched seed fraction seemed to have more inhibitory potency than gallic acid or ellagic acid.…”
Section: Discussionmentioning
confidence: 82%
“…Although D. longan leaves were reported to contain gallic acid, but the other active compounds for anti-aging in the leaf might be more potent than gallic acid due to the activities themselves or synergistic effects of other phenolic or active compounds consisting in the extracts. While inhibition of collagenase activity of D. longan leaf extract has not been reported to date, Panyathep et al (2013) revealed the inhibition of MMP-13 of D. longan seed extracts. The gallic acid-enriched and ellagic acid-enriched seed fraction seemed to have more inhibitory potency than gallic acid or ellagic acid.…”
Section: Discussionmentioning
confidence: 82%
“…The three compounds, GA, CGC and EP, obtained in our study are three typical phenolic compounds in plants which have been reported to possess strong antioxidant activity [ 26 , 27 ]. According to reports, free hydroxyl groups in phenolics are mainly responsible for antioxidant activity [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thailand [2]. The utilization of fruit waste by processing it into dietary fiber, which can be used as a food ingredient or diet supplement, has also been extensively studied [3].…”
Section: Raw Materialsmentioning
confidence: 99%